The Supercapacitor Degradation State Diagnostic System Based on LabVIEW - Hao, Meijuan; Wu, Lifeng; Guan, Yong; Pan, Wei; Tang, Wubing; Li, Xiaojuan (International Journal of Online and Biomedical Engineering (iJOE), 2013)
In this thesis, we design and implement the degradation state diagnostic system for supercapacitor. In order to detect the degradation degree of supercapacitor, it is necessary to test the changes of the parameters that include capacitance, ESR (equivalent series resistance) and the leakage current between the terminals of supercapacitor. The way to obtain these parameters is to measure the voltage and current value by the data acquisition card, and then transmit to the software of LabVIEW calculating the values. By comparing the values of capacitance and ESR with the original value separately, the degradation state of the supercapacitor can be estimated.